2018
DOI: 10.3390/min8050183
|View full text |Cite
|
Sign up to set email alerts
|

Catalan Imitations of the Ligurian Taches Noires Ware in Barcelona (18th–19th Century): An Example of Technical Knowledge Transfer

Abstract: The ware called Taches Noires was developed in Albisola (Liguria, NW Italy) during the 18th century. In just a few years, it spread all over the Mediterranean (Italy, France, Spain, Tunisia, and Greece) and also in the New World (Canada, the Caribbean Islands, and Mexico). The success of the Taches Noires ware was so massive that it was soon copied by Spanish and French workshops. A collection of Catalan imitations and Ligurian imports found in Barcelona were analysed and compared to previously existing data f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 7 publications
(17 citation statements)
references
References 7 publications
(9 reference statements)
2
14
0
1
Order By: Relevance
“…This mineral also indicates a firing temperature below 925 • C, while the Mn content is consistent with the original glaze recipe. Kentrolite was found near the glaze-body interface, suggesting an application of the pigment directly on the ceramic body in agreement with the original recipe [38].…”
Section: Technological and Provenance Markerssupporting
confidence: 81%
See 4 more Smart Citations
“…This mineral also indicates a firing temperature below 925 • C, while the Mn content is consistent with the original glaze recipe. Kentrolite was found near the glaze-body interface, suggesting an application of the pigment directly on the ceramic body in agreement with the original recipe [38].…”
Section: Technological and Provenance Markerssupporting
confidence: 81%
“…However, due to the fact that glass is opaque to electrons, SEM might not be the most suitable technique to investigate crystals embedded in glazes. Our pioneering studies focusing on the use of thin section samples have showed this limitation in contrast with OM that produced images much more useful to identify and interpret the processes that formed the crystallites [34][35][36][37][38]. Indeed, a very common situation in glaze microstructures is that the crystallites (either relics or neo-formed) can be found under the polished glaze surfaces.…”
Section: The State Of the Artmentioning
confidence: 99%
See 3 more Smart Citations